2012
DOI: 10.1017/s1755773911000312
|View full text |Cite
|
Sign up to set email alerts
|

Translating democracy: how activists in the European Social Forum practice multilingual deliberation

Abstract: Linguistic barriers may pose problems for politicians trying to communicate delicate decisions to a European-wide public, as well as for citizens wishing to protest at the European level. In this article I present a counter-intuitive position on the language question, one that explores how grassroots activists in social movements use translation as a novel practice to debate political alternatives in the European Union's (EU) multilingual public sphere. In recent years, new cross-European protest movements hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 29 publications
0
28
0
2
Order By: Relevance
“…Antisummit mobilizations across Europe are also multilingual events, but there is usually an abundance of English‐speaking activists and volunteer interpreters to facilitate communication effectively, if imperfectly. As Doerr (, ) shows in the case of the European Social Forum, when translation is practiced as an explicitly political act of horizontal prefiguration, in which the power of language is acknowledged and leveraged, then translation can make the decision‐making process more horizontal. Unlike the European Social Forum and World Social Forum (two other gatherings of the alterglobalization movement), however, antisummit mobilizations do not have an organized volunteer interpretation system.…”
Section: Dynamics Of Trust Miscommunication and Repressionmentioning
confidence: 99%
“…Antisummit mobilizations across Europe are also multilingual events, but there is usually an abundance of English‐speaking activists and volunteer interpreters to facilitate communication effectively, if imperfectly. As Doerr (, ) shows in the case of the European Social Forum, when translation is practiced as an explicitly political act of horizontal prefiguration, in which the power of language is acknowledged and leveraged, then translation can make the decision‐making process more horizontal. Unlike the European Social Forum and World Social Forum (two other gatherings of the alterglobalization movement), however, antisummit mobilizations do not have an organized volunteer interpretation system.…”
Section: Dynamics Of Trust Miscommunication and Repressionmentioning
confidence: 99%
“…My cross-national comparison of the Italian and British Social Forums illustrates that depending on the context, memories of violent symbolic exclusion in past movements account for the intensity, and timing of democratic crises in the national Social Forums I studied. In using Schwab's approach for my analysis of discourse and public storytelling, I found that the attempt to build dialogue and radical democracy in the Social Forums "clashed" at the very moment in which carrier groups publicized their "encrypted stories" of long-past symbolic exclusion (Doerr 2012). Carrier groups were experienced activists who remembered violent symbolic exclusion in previous decades' movements.…”
Section: An Example: Studying Encrypted Stories In Trans-generationalmentioning
confidence: 99%
“…66 Of course, language differences can complicate deliberation in a transnational partisan forum. Evidence from 67 fora of this kind (like the European Social Forum) shows however that these barriers can be overcome using professional translators (Doerr 2012).…”
mentioning
confidence: 99%